Influência da luz e temperatura em cavidades e canais secretores em plântulas de Copaifera langsdorffii Desf. (Leguminosae-Caesalpinioideae): estudo anatômico e ultraestrutural - Buarque, Plácido Fabrício Silva Melo [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Secretory spaces are distributed throughout the vegetative axis of Copaifera langsdorffii. They are constituted by uniseriate secretory epithelium and wide lumen, and represent a constitutive defense mechanism against herbivores and pathogens due to the produced secretion. In C. langsdorffii seedlings, oil cavities occur in the mesophyll of eophylls and in the cortex of epicotyl and hypocotyl, whereas oleoresin canals are present in the pith of epicotyl and hypocotyl. Evidences suggest that exogenous factors can influence the production of secretion in this species; however, nothing is known about these factors influencing the development of canals and cavities. This work aimed to investigate the influence of light and temperature on the density and lumen area of secretory canals and cavities in seedlings of C. langsdorffii, besides to study the influence of the temperature on the ultrastructural features of epithelial cells. Seedlings were maintained in climatic chamber under 2500lux, 1250lux and 250lux, and 15ºC, 25ºC and 35ºC. For quantitative anatomical analysis, samples of epicotyl and eophylls were processed according to usual techniques in plant anatomy. For ultrastructural studies, samples of eophylls were prepared following conventional techniques of transmission electron microscopy. Seedlings under 25ºC/1250lux presented higher density of cavities in eophylls and epicotyl, whereas seedlings under 25ºC/2500lux showed higher density of canals. This differential answer to light can be related to the distinctive origin of these secretory structures. Concerning the lumen area, variable answers were observed to cavities and canals. Ultrastructurally, epithelial cells of seedlings under 25ºC showed evidences of intense secretory activity. Alterations in mitochondria, plastids and endoplasmic reticulum were observed in seedlings under 15ºC and 35ºC. In seedlings under 35ºC, the epithelial cells showed evident signals of lysis, ...

Espaços secretores estão distribuídos por todo o eixo vegetativo de Copaifera langsdorffii. São constituídos por epitélio secretor unisseriado e lúmen amplo e, devido à secreção produzida, representam um mecanismo de defesa constitutivo contra herbívoros e patógenos. Nas plântulas desta espécie, cavidades secretoras de óleo ocorrem no mesofilo dos eofilos e no córtex do epicótilo e hipocótilo, enquanto que canais secretores de oleorresina estão presentes na medula do epicótilo e hipocótilo. Evidências sugerem que fatores exógenos podem influenciar na produção da secreção nessa espécie; entretanto, nada se conhece sobre a influência desses fatores no desenvolvimento de canais e cavidades. Este trabalho teve como objetivo investigar a influência da luz e da temperatura na densidade e na área do lúmen de cavidades e canais secretores em plântulas de C. langsdorffii, além de estudar a influência da temperatura na ultraestrutura das células epiteliais. Plântulas foram mantidas em câmara climática sob 2500lux, 1250lux e 250lux e 15ºC, 25ºC e 35ºC. Para análises anatômicas quantitativas, amostras do epicótilo e eofilos foram processadas segundo técnicas usuais em anatomia vegetal. Para análises ultraestruturais, amostras de eofilos foram preparadas de acordo com técnicas convencionais de microscopia eletrônica de transmissão. Plântulas mantidas sob 25ºC/1250lux mostraram maior densidade de cavidades nos eofilos e no epicótilo, enquanto aquelas mantidas sob 25ºC/2500lux apresentaram maior densidade de ...
Keywords: Anatomia vegetal; Botânica - Morfologia; Ultraestrutura (Biologia); Plantas - Efeito da luz; Arvores; Plants, Effect of light on